Characterisation of Intestinal Stem Cell Niche Constituents in Normal and Strangulated Equine Small Intestine. (9th September 2013) - Gonzalez, L.M.; Smith, L.; Blikslager, A.T.
Abstract : Aim: Death from colic results from acute circulatory failure secondary to intestinal ischaemia and sepsis. Multipotent stem cells normally reside within intestinal crypts and are the source of mucosal renewal that maintains barrier function. A better understanding of changes to intestinal cell populations during mucosal repair will facilitate future efforts directed at regenerative medicine. The aim of this research was to characterise the constituents of the stem cell niche in normal and strangulated equine intestine using biomarkers validated in other animal models. Methods: Tissues were collected from 3 healthy horses subjected to euthanasia for reasons unrelated to this project, and intra‐operatively from 2 horses admitted to the NCSU Veterinary Health Complex that required small intestinal resection. Tissues were examined using immunofluorescence (IF) and western blots (WB). For IF, fixed tissues were embedded and sectioned. Protein was isolated from snap frozen mucosal scrapings, and semi‐quantitative analysis of protein levels between groups was conducted using WB. Results: Stem/progenitor cells were labelled using sex determining region Y‐box 9 (SOX9), a marker of stem/progenitor cells, whereas the entire population of proliferative cells was identified by labelling proliferative cell nuclear antigen. Post mitotic cell types were labelled using mucin2 (goblet cells), chromogranin A (enteroendocrine cells), beta‐catenin (epithelial cells) and sucrase isomaltase (absorptive cells). Additionally, caspase 3 positively marked apoptotic cells. Western blot indicated increased apoptosis and decreased proliferation, but preservation of stem/progenitor cell populations in ischaemic cases. Sample collection continues on normal and ischaemic‐injured intestinal epithelium to support statistical differences. Conclusions and practical significance: These findings provide the technical platform for identifying distinct cell populations within the stem cell niche. These preliminary results indicate that surgically resected segments may be a viable source of stem/progenitor cells to induce regeneration in injured intestine. Ethical animal research: The Institutional Animal Care and Use Committee approved all animal studies and client consent was obtained.Sources of funding: 1) NJH/NCSU Comparative Medicine and Translational Research Training Program (CMTRTP) T32RR024394. 2) North Carolina Horse Council.Competing interests: None.